Фітотрофні анаморфні гриби Новгород-Сіверського Полісся - Андріанова, Т.В.; Голубцова, Ю.І. (Інститут ботаніки ім. М. Г. Холодного НАН України, 2006)
Впервые проведены детальные исследования фитотрофных анаморфных грибов Новгород-Сиверского Полесья (Черниговская и Сумская области). Анаморфные микромицеты представлены 31 видом из 15 родов Hyphomycetes и 88 видами из 32 родов Coelomycetes, зарегистрированных на 84 видах питающих растений 67 родов 38 семейств. За период 2003—2005 гг. отмечено 96 новых для территории исследования анаморфных микромицетов, 7 — новых для Украинского Полесья и 6 — новых для Левобережной Украины. Обнаружены также новые для Украины виды — Alysidium resinae (Fr.) M.B. Ellis var. microsporum B. Sutton, Bactridium flavum Kunze, Choanatiara lunata DiCosmo & Nag Raj, Cytoplacosphaeria rimosa (Oudem.) Petr., Fusicladium romellianum Ondrej, Phragmocephala elliptica (Berk. & Broome ) S. Hughes. Detailed survey of phytotrophic anamorphic fungi was carried out in the Novgorod-Sivers’k Polissia (Chernihiv and Sumy regions) for the first time. Anamorphic fungi are represented by 31 species of 15 genera of Hyphomycetes and 88 species of 32 genera of Coelomycetes reported on 84 species of host plants from 67 genera of 38 families. There have been collected 96 anamorphic fungi that are new for the Novgorod-Sivers’k Polissia, 7 anamorphic fungi that are new for the Ukrainian Polissia and 6 anamorphic fungi that are new for the left bank Dnieper river region of Ukraine in 2003—2005. There are new for the Ukraine species of Alysidium resinae (Fr.) M.B. Ellis var. microsporum B. Sutton, Bactridium flavum Kunze, Choanatiara lunata DiCosmo & Nag Raj, Cytoplacosphaeria rimosa (Oudem.) Petr., Fusicladium romellianum Ondøej, Phragmocephala elliptica (Berk. & Broome) S. Hughes.